2017
DOI: 10.2527/jas2017.1967
|View full text |Cite
|
Sign up to set email alerts
|

Improving the lean muscle color of dark-cutting beef by aging, antioxidant-enhancement, and modified atmospheric packaging1

Abstract: The objective was to evaluate the effects of wet-aging, rosemary-enhancement, and modified atmospheric packaging on the color of dark-cutting beef during simulated retail display. No-roll dark-cutting strip loins ( = 12; pH > 6.0) were selected from a commercial packing plant within 3 d postharvest. Using a balanced incomplete block design, dark-cutting loins were sectioned in half, and assigned to 1 of 3 aging periods: 7, 14, or 21 d. After respective aging, each aged section was divided into 3 equal parts, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
2
11
1
Order By: Relevance
“…Previous research indicated that light-exposed steaks packaged in nitrite-embedded film had lower redness than dark-storage steaks packaged in nitrite-embedded film ( Claus and Du, 2013 ). The antioxidant effects of rosemary in beef were noted by previous studies ( Sánchez-Escalante et al, 2003 ; Wills et al, 2017 ). Further, dark-cutting beef has lower moisture content than normal-pH beef.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…Previous research indicated that light-exposed steaks packaged in nitrite-embedded film had lower redness than dark-storage steaks packaged in nitrite-embedded film ( Claus and Du, 2013 ). The antioxidant effects of rosemary in beef were noted by previous studies ( Sánchez-Escalante et al, 2003 ; Wills et al, 2017 ). Further, dark-cutting beef has lower moisture content than normal-pH beef.…”
Section: Resultssupporting
confidence: 59%
“…In the present study, water treatment was included to determine the effects of water on reflectance properties. Water-enhancement increased lightness or L * values of ground beef ( Seyfert et al, 2007 ), normal-pH longissimus steaks ( Ramanathan et al, 2010 ), and dark-cutting steaks ( Wills et al, 2017 ); conversely minimal effect on lightness ( L * values) was observed in the current study.…”
Section: Resultscontrasting
confidence: 58%
See 2 more Smart Citations
“…For example, hydroxytyrosol, which has high free-radical-scavenging capabilities, caused increased in vivo force in aged rats [123]. Recent studies showed positive effects of resveratrol [124], some plant extracts ( Rhus coriaria [125] and Rosmarinus officinalis [126]), and vitamins (vitamin C [127]). The increasing number of similar studies nowadays shows the importance and topicality of finding good antioxidant treatment for the aged muscle.…”
Section: Antioxidant Therapies and Effects Of Exercise On The Agedmentioning
confidence: 99%